Rubber capable of rapidly expanding when encountering water and used for oil casing as well as preparation method and application of rubber
By using components such as nitrile rubber with acrylonitrile content, salt-resistant water-absorbing resin particles, coupling agents and foaming agents in petroleum casing rubber, the problem of water absorption speed of casing rubber is too slow, and the petroleum casing sleeve is realized Rapid expansion of the tube and enhanced cushioning and shock absorption.
Patent Information
- Application Number
- CN202310938471.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-28
AI Technical Summary
The water-expanded rubber used in existing petroleum casings absorbs water too slowly after being lowered at the well position, and cannot fully expand within a certain period of time, weakening its buffering and shock absorption function.
A rubber that rapidly expands with water in oil casing is prepared by nitrile rubber with medium acrylonitrile content, salt-resistant water-absorbing resin particles, coupling agents and foaming agents. This process improves the water absorption effect and expansion rate of the rubber, and enhances the performance in brine medium.
It significantly improves the water absorption expansion speed of rubber, ensures rapid expansion in petroleum casing applications, enhances its cushioning and shock absorption capabilities, and extends the service life of the casing.
Smart Images

Figure CN119431911A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-swellable rubber for petroleum casing, and particularly relates to a rubber for petroleum casing that rapidly swells when in contact with water, and a preparation method and application thereof. Background Art
[0002] Water-swelling rubber (WSR) is a new type of special rubber that can absorb water and expand in volume at a certain speed within a certain period of time in the presence of water. Therefore, it has both the high elasticity of rubber and the unique water-absorbing and swelling characteristics. The mechanism is that polar rubber is physically blended or grafted with strong hydrophilic components or groups. After encountering water, water molecules form a strong affinity with the hydrophilic group through physical effects such as diffusion, capillary and surface adsorption, and the water molecules are wrapped in the rubber to achieve exponential expansion of volume and mass. When the stress resisting deformation and the osmotic pressure difference reach a balance, the water-absorbing rubber maintains a relatively stable elastic pressure-bearing buffering and plugging effect.
[0003] Oil casing is mainly used to support the well wall during drilling and after completion to ensure the normal operation of the drilling process and the entire oil well after completion. Oil casing is the lifeline for maintaining the operation of oil wells. Once the casing itself is damaged for some reason, it may lead to a reduction in production of the entire well or even scrapping. Due to different geological conditions, the stress state downhole is complex, and the tensile, compressive, bending and torsion stresses act on the pipe body, which puts higher requirements on the quality of the casing itself. In actual work, the casing is very easy to deform due to the complex stress, which directly affects the quality and efficiency of the operation. For this reason, some manufacturers have proposed a number of countermeasures, including increasing the steel grade and thickness of the casing to improve the mechanical strength of the casing, but the effect of preventing casing deformation is limited. The patent disclosed by Xiang Degui et al. (2018) adopts an innovative technical idea. While the outer diameter of the casing changes, the inner diameter remains unchanged, which can keep the wellbore intact for a period of time. The casing is coated with water-swelling rubber. Its specific working principle is: the water-swelling rubber is coated on the outer wall of the casing. After reaching the well site, the water-swelling rubber absorbs water and expands, and the rubber layer thickens exponentially. Since the rubber has certain flexibility and viscoelasticity, it has a very high elastic deformation capacity at this time. When subjected to various impact forces brought by the formation, the rubber undergoes elastic deformation within a certain range to absorb and disperse part of the impact force. The rubber can also gather the impact force to a local area and undergo elastic deformation in this area, thereby gradually releasing the energy. In addition, the molecules inside the rubber will move relative to each other due to shearing, thereby consuming part of the energy of the impact force. The above processes can slow down the transmission of impact force and play a buffering and shock-absorbing role.
[0004] However, the current use of water-swelling rubber in casings to prevent deformation still has certain defects. The reason is that: as a macromolecular network structure, water-swelling rubber has strong attraction between its molecules and exhibits a certain tensile strength on a macro scale. Therefore, in the process of absorbing water, it is actually a process of swelling due to water absorption and overcoming the molecular attraction. Therefore, the expansion effect, especially the initial expansion speed, is extremely slow. Specifically, water-absorbing self-swelling rubber generally has mechanical blending type and chemical grafting type, and its expansion ratio can be divided into high expansion ratio of more than 3.5 times, medium expansion ratio of 2 to 3.5 times and low expansion ratio of 0.5 to 2 times. At the same time, the water absorption effect of rubber is greatly affected by temperature, medium and water-contacting area, especially in salt water. Due to the strong bond between salt ions and water molecules, the hydrophilic group of macromolecular covalent bonds is weak in the process of water capture. In addition, the structural characteristics of the casing product greatly reduce the rubber contact area with water, and the expansion of the rubber tube becomes a single-sided restricted expansion. The water absorption rate and saturated water absorption rate of the rubber are reduced exponentially, which ultimately leads to the fact that in actual application, the casing rubber lowered to the well site cannot be fully expanded within a certain period of time due to the slow water absorption speed, thus weakening its buffering and shock-absorbing function. Therefore, in order to effectively prevent casing deformation, it is necessary to increase the expansion rate of water-expandable rubber after it is lowered to the well site.
[0005] In terms of increasing the water absorption speed, patent CN101139448A designs a method of using fibers to improve the water absorption speed of water-swelling rubber. The water absorption speed of water-swelling rubber can be increased by adding short fibers, but the specific product application requirements are not considered. First, the combined casing is to add a layer of water-absorbing rubber to the outer wall of the casing. The rubber has a certain thickness, and the only part that can touch the water is the outermost surface. The water-absorbing rubber designed by this method is not effective in increasing the water absorption speed when applied to the casing. Second, the water-absorbing rubber designed by this method has increased the tensile strength through the fibers, but in the casing application, the higher tensile strength becomes a resistance to the rapid water absorption and expansion of the rubber, further affecting the actual effect in the casing. Summary of the invention
[0006] In order to solve the deficiencies of the prior art, the present invention provides a rubber for oil casing that rapidly swells when exposed to water, and a preparation method and application thereof. The present invention solves the problem that the existing rubber swells slowly when absorbing water, so that the rubber that swells when exposed to water can be effectively used in oil casing.
[0007] The technical solution provided by the present invention is as follows:
[0008] A method for preparing water-swelling rubber for petroleum casing, characterized in that it comprises the following steps:
[0009] 1) obtaining raw materials, including the following components in parts by weight: 100 parts of nitrile rubber, 60-80 parts of reinforcing agent, 0-5 parts of antioxidant, 3-10 parts of plasticizer, 1.2-3 parts of cross-linking agent, 2-6 parts of cross-linking aid, 80-120 parts of salt-resistant water-absorbing resin, 1-3 parts of coupling agent, and 8-30 parts of foaming agent;
[0010] 2) Mix the nitrile rubber, reinforcing agent and plasticizer according to the above proportions, and knead them at a temperature range of 80 to 120° C. for 5.5 to 6 minutes;
[0011] 3) Add antioxidant, salt-resistant water-absorbing resin, coupling agent, foaming agent and cross-linking agent in the above proportions, mix and knead at 75-85°C for 4-5 minutes;
[0012] 4) Finally, add the cross-linking agent according to the above ratio, mix and knead for 3-4 minutes at a temperature of 70-90°C, and then discharge the material to obtain the rubber for oil casing that expands rapidly when in contact with water.
[0013] In the above technical solution:
[0014] The use of nitrile rubber with medium acrylonitrile content can improve the compatibility with plasticizers, facilitate the dispersion of water-absorbing resin, and thus improve the water absorption effect of rubber;
[0015] The introduction of salt-resistant water-absorbing resin can passivate the sensitivity of rubber to the water properties of the medium and improve the water absorption capacity of rubber in salt water medium;
[0016] The introduction of coupling agent can promote the compatibility of salt-resistant water-absorbing resin particles with the rubber matrix, prevent the aggregation of particles, promote the uniform dispersion of water-absorbing resin and reinforcing agent in the rubber body, and further ensure the effective use of water-absorbing resin and the increase of the swelling speed of rubber when it comes into contact with water;
[0017] The foaming structure can shorten the time that the rubber inner layer contacts water.
[0018] Through the coordination of the above-mentioned means, the water swelling speed of the water-absorbing rubber is increased, so that the application of the water-swellable rubber in the oil casing has obvious advantages.
[0019] In addition, the addition of plasticizers improves the fluidity of rubber; cross-linking agents improve the mechanical properties of rubber.
[0020] Specifically, the nitrile rubber is a nitrile rubber with a combined acrylonitrile content of 25-30%, which can be selected from the prior art, for example, JSR N240S from Japan and FRN501 from the United States.
[0021] Specifically, the reinforcing agent is a mixture of quick-pressed carbon black and fumed silica in a weight ratio of (15-20): (45-60). Quick-pressed carbon black can be selected from the prior art, for example, ExxonMobil's The XC-72 product of Jiangxi Black Cat Carbon Black Co., Ltd., the Black Cat N550 carbon black of Jiangxi Black Cat Carbon Black Co., Ltd. The fumed silica can be selected from the existing technology, for example, Kruss's Brand 160V product; Shanghai Cabot Chemical Co., Ltd., Cabot CABOT, CAB-O-SILLM150.
[0022] Specifically, the antioxidant is a mixture of 2,2,4-trimethyl-1,2-dihydroquinoline polymer and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline in a weight ratio of (0-2):(0-3). The 2,2,4-trimethyl-1,2-dihydroquinoline polymer can be selected from the prior art, for example, Corning's Brand PC-1000 products.
[0023] Specifically, the plasticizer is dioctyl sebacate, diundecyl phthalate or ethylene glycol monolaurate.
[0024] Specifically, the cross-linking agent is sulfur powder, which can be selected from the prior art, for example, AkzoNobel brand Sulphur Powder product of AkzoNobel.
[0025] Specifically, the crosslinking aid is a mixture of tetraethylthiuram disulfide and 2-thiolbenzothiazole in a weight ratio of (0.5-1.5):(1.5-4.5).
[0026] Specifically, the salt-resistant water-absorbing resin is a sodium polyacrylate super absorbent resin, an acrylamide super absorbent resin, or a mixture of the two in a weight ratio of (60-90):(20-30). The salt-resistant water-absorbing resin can be selected from the prior art, for example, a sodium polyacrylate super absorbent resin product of the Lupasol WF brand of BASF SE, an acrylamide super absorbent resin product of the Aqua Keep AM brand of Sumitomo Seika Chemicals Co., Ltd.
[0027] Specifically, the coupling agent is at least one of vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane or γ-methacryloxypropyl trimethoxysilane.
[0028] Specifically, the foaming agent is azodicarbonamide or hydrazine p-toluenesulfonate, or a mixture of the two.
[0029] Preferably, the reinforcing agent is a mixture of quick-pressed black and fumed silica in a weight ratio of 1:3. The reason for using the mixture of the two in this ratio is to obtain a certain strength while better improving the processing performance of the rubber.
[0030] Preferably, the antioxidant is a mixture of 2,2,4-trimethyl-1,2-dihydroquinoline polymer and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline in a weight ratio of 1:1.5. The reason for using such a ratio of the two is to obtain a greater synergistic effect and further improve the ability to resist flex cracking.
[0031] Preferably, the crosslinking aid is a mixture of tetraethylthiuram disulfide and 2-thiol benzothiazole in a weight ratio of 1:3. The reason for using the mixture of the two in this ratio is to obtain a suitable vulcanization speed by using the primary and secondary crosslinking aids together.
[0032] Preferably, the salt-resistant water-absorbing resin is a mixture of the two alone or in a weight ratio of 3: 1. The reason for using the two mixed is that the combined use can improve the compatibility in rubber.
[0033] Furthermore, the method further comprises step 5), wherein the rubber compound for oil casing obtained in step 4) is packaged and rolled at a thickness of 1.5-2 mm on a mixing mill at a temperature below 100° C., and the roll spacing is adjusted to obtain a sheet of rubber compound for oil casing. Afterwards, the rubber compound obtained in the above step can be vulcanized at a temperature of (160-180)° C.×(12-18) min.
[0034] Based on the above technical solution, the sheet material can be directly used in the process of making oil casing after being made into sheet material.
[0035] The invention also provides the prepared rubber for petroleum casing which swells rapidly when in contact with water.
[0036] The invention also provides application of rubber that rapidly expands when in contact with water for oil casing, which is used for making oil casing.
[0037] Specifically, it is used for gluing to the surface of steel oil casing as a water-absorbing rubber layer.
[0038] The water-swellable rubber provided by the present invention can be directly fixed to the outer wall of the oil casing by an adhesive during molding, and the combined oil casing can be molded in one step. The steps are simple, and quantitative production can be realized without changing the existing oil casing downhole operation process, thereby ensuring the promotion and application of the new oil casing downhole, improving the feasibility and safety of the expansion rubber application, and finally realizing the self-protection of the oil casing.
[0039] Compared with the prior art, the present invention has the following advantages:
[0040] The water-expanding rubber provided by the present invention can significantly improve the expansion rate of rubber for oil casing. By adopting nitrile rubber with medium propylene content and salt-resistant water-absorbing resin particles, the sensitivity of the rubber to the water properties of the medium is passivated, and the expansion rate in salt water is greatly improved. The effective use of the foaming agent increases the number of gaps in the rubber network structure, improves the water penetration rate of the rubber, increases the water contact area of the thick product under one-way water contact, shortens the water contact time of the matrix in the rubber belt that contacts the oil casing, and significantly improves the water absorption and expansion rate of the entire rubber. The introduction of coupling agents and plasticizers promotes the uniform dispersion of salt-resistant water-absorbing resins and reinforcing agents in the rubber body, further ensuring the effective use of water-absorbing resins and the improvement of the expansion rate of rubber when exposed to water. The preparation process of this type of rubber is simple, the product molding difficulty is small, and the damage form of the oil casing during the operation process can be optimized, thereby improving the service life of the oil casing.
[0041] Specific effects of the invention:
[0042] The water-expanding rubber provided by the present invention is mixed and vulcanized according to the above preparation process and tested according to the corresponding standards. The representative test data obtained include tensile strength ≥4MPa, hardness ≥70ShoreA, tear strength ≥20kN / m, volume expansion rate of 20mm×20mm×2mm sample ≥3 times after soaking in high-temperature water at 100°C for 4 hours, and saturation expansion time <1 day. After soaking in high-temperature salt water at 100°C for 4 hours, the weight expansion multiple of the rubber cylinder with a diameter of 20cm×height of 30cm×thickness of 5cm is ≥1 times. The salt-resistant water-absorbing resin particles are introduced to better adapt to the expansion of the underground cement slurry environment. The coupling agent is adopted to promote the compatibility of the salt-resistant water-absorbing resin particles with the rubber matrix, prevent the aggregation of the particles, and further realize the maximum efficiency of the hydrophilic group. The preferred foaming agent naturally forms a large number of void structures inside the rubber, providing conditions for the rubber body to quickly contact water at the part away from the surface cement slurry. The preparation process of the water-expanding rubber in the present invention is simple. It is coated on the outside of the base pipe and expands rapidly in the cement slurry environment. Its excellent high elasticity reduces the influence of fault sliding on the shear deformation of the oil casing. The expansion rubber converts and consumes the extremely non-uniform external extrusion load energy that may be generated in the multi-stage fracturing process, which is better than the buffer spring. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 3 is a comparison chart of various conventional physical properties of the embodiments of the present invention and the comparative examples, wherein from left to right they correspond to embodiments 1, 2, 3 and comparative examples 1, 2, 3.
[0044] Figure 2 3 is a comparison chart of various water absorption and expansion properties of the embodiments of the present invention and the comparative examples, wherein from left to right they correspond to embodiments 1, 2, 3 and comparative examples 1, 2, 3. DETAILED DESCRIPTION
[0045] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0046] Example 1
[0047] The present embodiment provides a rubber that rapidly swells when in contact with water, and the formula thereof is 100 parts of nitrile rubber JSRN240S, 20 parts of carbon black N550, 60 parts of white carbon black CABOT, 2 parts of antioxidant RD, 3 parts of antioxidant AW, 2 parts of sulfur, 1.5 parts of accelerator M, 0.5 parts of TETD, 4 parts of DOS, 100 parts of SAP, 2 parts of KH-570, and 10 parts of Aceto AD.
[0048] The mixed rubber was prepared according to the above mixing method. After standing for 16 hours, it was vulcanized on a flat vulcanizer at 170℃×15min. The rubber sample was taken out and stood at room temperature for 24 hours. The tensile strength was 5.4MPa, the elongation at break was 430%, the tear strength was 31kN / m, and the hardness was 78ShoreA. After being immersed in high-temperature water at 100℃ for 4 hours, the volume expansion rate of a 20mm×20mm×2mm sample was 300%, the equilibrium saturation expansion time was 23 hours, and the equilibrium saturation expansion rate was 610%.
[0049] An oil immersion test of a film with a size of 20cm×20cm×2cm was carried out to complete free expansion. The oil sample was an oil-based drilling fluid for shale gas wells. The immersion temperature was room temperature, the pressure was 0 MPa, and the time was 48 hours. A wide-mouth bottle was used. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 1 had a room temperature and high temperature weight expansion multiple of 0.07 times in the free state in the static oil-based mud.
[0050] A rubber cylinder with a size of 20 cm in diameter × 30 cm in height × 5 cm in thickness was immersed in water to complete shape-constrained expansion. The water sample was distilled water, the immersion temperature was 100°C, the pressure was 1 MPa, the time was 4 h, and the high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 1 had a shape-constrained weight expansion multiple of 2.2 times in the static distilled water used.
[0051] A rubber cylinder with a size of 20 cm in diameter × 30 cm in height × 5 cm in thickness was immersed in salt water to complete shape-constrained expansion. The water sample was a 2% KCL solution. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 1 had a shape-constrained weight expansion multiple of 1.3 times in the static 2% KCL solution used.
[0052] A slurry test was conducted on a film of size 20 cm×20 cm×2 cm to complete free expansion. The medium used was cement slurry for cementing with a slow-release agent added. The immersion temperature was 100° C., the pressure was 100 MPa, the time was 4 h, and the high-temperature experimental equipment was a pressurized high-frequency stirring high-temperature furnace. The water-swellable rubber provided in Example 1 had a weight expansion multiple of 1.1 times in the free state in the dynamic cement slurry used.
[0053] Example 2
[0054] The present embodiment provides a rubber that swells rapidly when in contact with water, and the formula of the rubber is 100 parts of nitrile rubber JSRN240S, 15 parts of carbon black N550, 45 parts of white carbon black CABOT, 1 part of anti-RD, 1.5 parts of anti-AW, 3 parts of sulfur, 1.5 parts of promoter M, 0.5 parts of TETD, 6 parts of DOS, 120 parts of SAP, 2 parts of A-151, and 15 parts of Aceto AD.
[0055] The mixed rubber was prepared according to the above mixing method. After standing for 16 hours, it was vulcanized on a flat vulcanizer at 170℃×15min. The rubber sample was taken out and stood at room temperature for 24 hours. The tensile strength was 5.1MPa, the elongation at break was 550%, the tear strength was 35kN / m, and the hardness was 74ShoreA. After being immersed in high-temperature water at 100℃ for 4 hours, the volume expansion rate of a 20mm×20mm×2mm sample was 320%, the equilibrium saturation expansion time was 22 hours, and the equilibrium saturation expansion rate was 650%.
[0056] An oil immersion test of a film with a size of 20cm×20cm×2cm was carried out to complete free expansion. The oil sample used was oil-based drilling fluid for shale gas wells. The immersion temperature was room temperature, the pressure was 0 MPa, and the time was 48 hours. A wide-mouth bottle was used. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 2 had a room temperature and high temperature weight expansion multiple of 0.08 times in the static oil-based mud in the free state.
[0057] A rubber cylinder with a size of 20 cm in diameter × 30 cm in height × 5 cm in thickness was immersed in water to complete shape-constrained expansion. The water sample was distilled water, the immersion temperature was 100°C, the pressure was 1 MPa, the time was 4 h, and the high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 2 had a shape-constrained weight expansion multiple of 2.1 times in the static distilled water used.
[0058] A rubber cylinder with a size of 20 cm in diameter × 30 cm in height × 5 cm in thickness was immersed in salt water to complete shape-constrained expansion. The water sample was a 2% KCL solution. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 2 had a shape-constrained weight expansion multiple of 1.5 times in the static 2% KCL solution used.
[0059] A slurry test was conducted on a film of size 20 cm×20 cm×2 cm to complete free expansion. The medium used was cement slurry for cementing with a slow-release agent added. The immersion temperature was 100° C., the pressure was 100 MPa, the time was 4 h, and the high-temperature experimental equipment was a pressurized high-frequency stirring high-temperature furnace. The water-swellable rubber provided in Example 2 had a weight expansion multiple of 1.1 times in the free state in the dynamic cement slurry used.
[0060] Example 3
[0061] The present embodiment provides a rubber that swells rapidly when in contact with water, and the formula of the rubber is 100 parts of nitrile rubber JSRN240S, 15 parts of carbon black N550, 45 parts of white carbon black CABOT, 1 part of anti-RD, 1.5 parts of anti-AW, 1.3 parts of sulfur, 3 parts of promoter M, 1 part of TETD, 6 parts of DOS, 120 parts of SAP, 2 parts of A-172, and 12 parts of Aceto AD.
[0062] The mixed rubber was prepared according to the above mixing method. After standing for 16 hours, it was vulcanized on a flat vulcanizer at 170℃×15min. The rubber sample was taken out and stood at room temperature for 24 hours. The tensile strength was 4.2MPa, the elongation at break was 530%, the tear strength was 28kN / m, and the hardness was 72ShoreA. After being immersed in high-temperature water at 100℃ for 4 hours, the volume expansion rate of a 20mm×20mm×2mm sample was 360%, the equilibrium saturation expansion time was 18 hours, and the equilibrium saturation expansion rate was 665%.
[0063] An oil immersion test was carried out on a film of size 20cm×20cm×2cm to complete free expansion. The oil sample used was oil-based drilling fluid for shale gas wells. The immersion temperature was room temperature, the pressure was 0 MPa, and the time was 48 hours. A wide-mouth bottle was used. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 3 had a room temperature and high temperature weight expansion multiple of 0.07 times in the static oil-based mud in the free state.
[0064] A water immersion test of a rubber cylinder with dimensions of 20 cm in diameter × 30 cm in height × 5 cm in thickness was carried out to complete shape-constrained expansion. The water sample was distilled water, the immersion temperature was 100°C, the pressure was 1 MPa, the time was 4 hours, and the high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 3 had a shape-constrained weight expansion multiple of 2.2 times in the static distilled water used.
[0065] A rubber cylinder with a size of 20 cm in diameter × 30 cm in height × 5 cm in thickness was immersed in salt water to complete shape-constrained expansion. The water sample was a 2% KCL solution. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 3 had a shape-constrained weight expansion multiple of 1.6 times in the static 2% KCL solution used.
[0066] A 20 cm × 20 cm × 2 cm film was immersed in cement slurry to complete free expansion. The medium used was cement slurry with a slow-release agent added. The immersion temperature was 100° C., the pressure was 100 MPa, and the time was 4 h. The high-temperature experimental equipment was a pressurized high-frequency stirring high-temperature furnace. The water-swellable rubber provided in Example 3 had a weight expansion multiple of 1.2 times in the free state in the dynamic cement slurry used.
[0067] Comparative Example 1
[0068] The present comparative example provides a water-swellable rubber, whose formula is 100 parts of nitrile rubber JSRN230S, 20 parts of carbon black N550, 60 parts of white carbon black CABOT, 2 parts of anti-RD, 3 parts of anti-AW, 2 parts of sulfur, 1.5 parts of promoter M, 0.5 parts of TETD, 4 parts of DOS, 100 parts of SAP, 2 parts of KH-570, and 10 parts of Aceto AD.
[0069] The mixed rubber was prepared according to the above mixing method. After standing for 16 hours, it was vulcanized on a flat vulcanizer at 170℃×15min. The rubber sample was taken out and stood at room temperature for 24 hours. The tensile strength was 8.7MPa, the elongation at break was 230%, the tear strength was 35kN / m, and the hardness was 80ShoreA. After being immersed in high-temperature water at 100℃ for 4 hours, the volume expansion rate of a 20mm×20mm×2mm sample was 228%, the equilibrium saturation expansion time was 36 hours, and the equilibrium saturation expansion rate was 350%.
[0070] An oil immersion test of a film with a size of 20cm×20cm×2cm was carried out to complete free expansion. The oil sample was an oil-based drilling fluid for shale gas wells. The immersion temperature was room temperature, the pressure was 0 MPa, and the time was 48 hours. A wide-mouth bottle was used. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 1 had a room temperature and high temperature weight expansion multiple of 0.11 times in the free state in the static oil-based mud.
[0071] A water immersion test of a rubber cylinder with dimensions of 20 cm in diameter × 30 cm in height × 5 cm in thickness was carried out to complete shape-constrained expansion. The water sample was distilled water, the immersion temperature was 100°C, the pressure was 1 MPa, the time was 4 hours, and the high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 1 had a shape-constrained weight expansion multiple of 0.9 times in the static distilled water used.
[0072] A rubber cylinder with a size of 20 cm in diameter × 30 cm in height × 5 cm in thickness was immersed in salt water to complete shape-constrained expansion. The water sample was a 2% KCL solution. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 1 had a shape-constrained weight expansion multiple of 0.5 times in the static 2% KCL solution used.
[0073] A slurry test was conducted on a film of size 20 cm×20 cm×2 cm to complete free expansion. The medium used was cement slurry with a slow-release agent added. The immersion temperature was 100° C., the pressure was 100 MPa, the time was 4 h, and the high-temperature experimental equipment was a pressurized high-frequency stirring high-temperature furnace. The water-swellable rubber provided in Example 1 had a weight expansion multiple of 0.6 times in the free state in the dynamic cement slurry used.
[0074] By comparing with the examples, it can be seen that the change of the acrylonitrile content in the nitrile rubber can significantly affect the expansion ratio and expansion rate of the expandable rubber.
[0075] Comparative Example 2
[0076] The present comparative example provides a water-swellable rubber, whose formula is 100 parts of nitrile rubber JSRN240S, 15 parts of carbon black N550, 45 parts of white carbon black CABOT, 1 part of anti-RD, 1.5 parts of anti-AW, 3 parts of sulfur, 1.5 parts of promoter M, 0.5 parts of TETD, 6 parts of DOS, 20 parts of SAP, 2 parts of A-151, and 15 parts of Aceto AD.
[0077] The mixed rubber was prepared according to the above mixing method. After standing for 16 hours, it was vulcanized on a flat vulcanizer at 170℃×15min. The rubber sample was taken out and stood at room temperature for 24 hours. The tensile strength was 7.8MPa, the elongation at break was 680%, the tear strength was 20kN / m, and the hardness was 58ShoreA. After being immersed in high-temperature water at 100℃ for 4 hours, the volume expansion rate of a 20mm×20mm×2mm sample was 100%, the equilibrium saturation expansion time was 49 hours, and the equilibrium saturation expansion rate was 320%.
[0078] An oil immersion test was carried out on a film of size 20cm×20cm×2cm to complete free expansion. The oil sample was oil-based drilling fluid for shale gas wells. The immersion temperature was room temperature, the pressure was 0 MPa, and the time was 48 hours. A wide-mouth bottle was used. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 2 had a room temperature and high temperature weight expansion multiple of 0.06 times in the static oil-based mud in the free state.
[0079] A water immersion test of a rubber cylinder with dimensions of 20 cm in diameter × 30 cm in height × 5 cm in thickness was carried out to complete shape-constrained expansion. The water sample was distilled water, the immersion temperature was 100°C, the pressure was 1 MPa, the time was 4 hours, and the high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 2 had a shape-constrained weight expansion multiple of 0.8 times in the static distilled water used.
[0080] A rubber cylinder with a size of 20 cm in diameter × 30 cm in height × 5 cm in thickness was immersed in salt water to complete shape-constrained expansion. The water sample was a 2% KCL solution. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 2 had a shape-constrained weight expansion multiple of 0.4 times in the static 2% KCL solution used.
[0081] A 20 cm × 20 cm × 2 cm film was immersed in cement slurry to complete free expansion. The medium used was cement slurry with a slow-release agent added. The immersion temperature was 100° C., the pressure was 100 MPa, the time was 4 h, and the high-temperature experimental equipment was a pressurized high-frequency stirring high-temperature furnace. The water-swellable rubber provided in Example 2 had a weight expansion multiple of 0.4 times in the free state in the dynamic cement slurry used.
[0082] By comparing with the examples, it can be seen that the reduction in the amount of salt-resistant water-absorbing resin significantly affects the time and expansion speed of the expanded rubber to reach water absorption equilibrium saturation.
[0083] Comparative Example 3
[0084] This comparative example provides a water-swellable rubber, whose formula is 100 parts of nitrile rubber JSRN240S, 15 parts of carbon black N550, 45 parts of white carbon black CABOT, 1 part of anti-RD, 1.5 parts of anti-AW, 1.3 parts of sulfur, 3 parts of promoter M, 1 part of TETD, 6 parts of DOS, 120 parts of SAP, and 12 parts of Aceto AD.
[0085] The rubber mixture was prepared according to the above mixing method. After standing for 16 hours, it was vulcanized on a flat vulcanizer at 170℃×15min. The rubber sample was taken out and stood at room temperature for 24 hours. The tensile strength was 4.0MPa, the elongation at break was 450%, the tear strength was 24kN / m, and the hardness was 69ShoreA. After being immersed in high-temperature water at 100℃ for 4 hours, the volume expansion rate of a 20mm×20mm×2mm sample was 260%, the equilibrium saturation expansion time was 20 hours, and the equilibrium saturation expansion rate was 430%.
[0086] An oil immersion test was carried out on a film of size 20cm×20cm×2cm to complete free expansion. The oil sample used was oil-based drilling fluid for shale gas wells. The immersion temperature was room temperature, the pressure was 0 MPa, and the time was 48 hours. A wide-mouth bottle was used. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 3 had a room temperature and high temperature weight expansion multiple of 0.07 times in the static oil-based mud in the free state.
[0087] A rubber cylinder with a size of 20 cm in diameter × 30 cm in height × 5 cm in thickness was immersed in water to complete shape-constrained expansion. The water sample was distilled water, the immersion temperature was 100°C, the pressure was 1 MPa, the time was 4 h, and the high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 3 had a shape-constrained weight expansion multiple of 1.7 times in the static distilled water used.
[0088] A rubber cylinder with a size of 20 cm in diameter × 30 cm in height × 5 cm in thickness was immersed in salt water to complete shape-constrained expansion. The water sample was a 2% KCL solution. The immersion temperature was 100°C, the pressure was 1 MPa, and the time was 4 hours. The high-temperature experimental equipment was a pressurized high-temperature furnace. The water-swellable rubber provided in Example 3 had a shape-constrained weight expansion multiple of 0.9 times in the static 2% KCL solution used.
[0089] A slurry test was conducted on a film of size 20 cm×20 cm×2 cm to complete free expansion. The medium used was cement slurry for cementing with a slow-release agent added. The immersion temperature was 100° C., the pressure was 100 MPa, the time was 4 h, and the high-temperature experimental equipment was a pressurized high-frequency stirring high-temperature furnace. The water-swellable rubber provided in Example 3 had a weight expansion multiple of 0.5 times in the dynamic cementing slurry used in the free state.
[0090] By comparing with the examples, it can be seen that the addition amount of the coupling agent is 0 parts, which reduces the strength of the expanded rubber, reflecting that the salt-resistant water-absorbing resin is unevenly dispersed, resulting in a significant decrease in the water absorption rate.
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a rubber that rapidly swells in water for petroleum casing, characterized in that: The following steps are involved: 1) obtaining raw materials, including the following components in parts by weight: 100 parts of nitrile rubber, 60-80 parts of reinforcing agent, 0-5 parts of antioxidant, 3-10 parts of plasticizer, 1.2-3 parts of cross-linking agent, 2-6 parts of cross-linking aid, 80-120 parts of salt-resistant water-absorbing resin, 1-3 parts of coupling agent, and 8-30 parts of foaming agent; 2) Mix the nitrile rubber, reinforcing agent and plasticizer according to the above proportions, and knead them at a temperature range of 80 to 120° C. for 5.5 to 6 minutes; 3) Add antioxidant, salt-resistant water-absorbing resin, coupling agent, foaming agent and cross-linking agent in the above proportions, mix and knead at 75-85°C for 4-5 minutes; 4) Finally, add the cross-linking agent according to the above ratio, mix and knead for 3-4 minutes at a temperature of 70-90°C, and then discharge the material to obtain the rubber for oil casing that expands rapidly when in contact with water.
2. The method for preparing the water-swelling rubber for petroleum casing according to claim 1, characterized in that: The nitrile rubber is a nitrile rubber having a combined acrylonitrile content of 25-30%; The reinforcing agent is a mixture of quick-pressed black and fumed silica in a weight ratio of (15-20):(45-60); The antioxidant is a mixture of 2,2,4-trimethyl-1,2-dihydroquinoline polymer and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline in a weight ratio of (0-2):(0-3); The plasticizer is dioctyl sebacate, diundecyl phthalate or ethylene glycol monolaurate; The cross-linking agent is sulfur powder; The crosslinking aid is tetraethylthiuram disulfide and 2-thiol benzothiazole. A mixture of a weight ratio of (0.5-1.5):(1.5-4.5); The salt-resistant water-absorbing resin is a sodium polyacrylate super absorbent resin, an acrylamide super absorbent resin, or a mixture of the two in a weight ratio of (60-90):(20-30); The coupling agent is at least one of vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane or γ-methacryloxypropyl trimethoxysilane; The foaming agent is azodicarbonamide or hydrazine p-toluenesulfonate or a mixture of the two.
3. The method for preparing the water-swelling rubber for petroleum casing according to claim 2, characterized in that: The reinforcing agent is a mixture of quick-pressed black and fumed silica in a weight ratio of 1:
3.
4. The method for preparing the water-swelling rubber for petroleum casing according to claim 2, characterized in that: The antioxidant is a mixture of 2,2,4-trimethyl-1,2-dihydroquinoline polymer and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline in a weight ratio of 1:1.
5.
5. The method for preparing the water-swelling rubber for petroleum casing according to claim 2, characterized in that: The cross-linking auxiliary agent is a mixture of tetraethylthiuram disulfide and 2-thiol benzothiazole in a weight ratio of 1:
3.
6. The method for preparing the water-swelling rubber for petroleum casing according to claim 2, characterized in that: The salt-resistant water-absorbing resin is used alone or mixed in a weight ratio of 3:
1.
7. The method for preparing the water-swelling rubber for petroleum casing according to any one of claims 1 to 6, characterized in that: The method further comprises step 5), wherein the rubber compound for oil casing that rapidly swells when in contact with water obtained in step 4) is packaged and rolled at a temperature below 100° C. with a thickness of 1.5-2 mm on a mixing mill, and the roll spacing is adjusted to obtain a sheet of rubber compound for oil casing that rapidly swells when in contact with water.
8. A rubber for oil casing that rapidly swells in contact with water, prepared according to the preparation method according to any one of claims 1 to 7.
9. An application of the water-swelling rubber for petroleum casing according to claim 8, characterized in that: Used to make oil casing.
10. The use according to claim 9, characterized in that: Used to glue to the surface of steel oil casing as a water-absorbing rubber layer.
Citation Information
Patent Citations
Method for improving absorption speed of water swelling rubber by employing fibre
CN101139448A